Anthropic Activities in Ribeirão das Pedras Drainage Basin, São Paulo State, Brazil - Lorandi, Reinaldo; Dos Santos, Franciane Mendonça; Di Lollo, José Augusto [UNESP] (Revista Brasileira de Geografia Fisica, 2019)
Geoenvironmental zoning is an instrument widely used in the environmental planning of river basins, especially with regard to urban expansion. In this context, the objective of this study was to prepare a 1:50,000-scale chart of the contamination potential of aquifers for the Ribeirão das Pedras watershed, located in Sao Paulo state, Brazil. This river basin comprises an area of 111.47 km2, most of it located in the municipality of Santa Cruz das Palmeiras, with some smaller portions in the municipalities of Tambau, Pirassununga, and Porto Ferreira. The following procedures were conducted for the preparation of this cartographic document: Delimitation of the catchment area based on the articulation of topographic charts using the Geographic Information System (SIG) ArcGis® 10.3 software; preparation of a map of geological formations of the basin; and classification of the contamination potential by multicriteria analysis including five classes: Very low, low, medium, high, and very high. As a result, a chart of contamination potential was produced showing that the high and very high potential classes comprised 36.31% of the catchment area, where the aquifer units present high water flow and storage capacity; the low and very low potentials are located on the Basic Intrusive and Corumbatai aquifer units, with characteristics that limit the capacity of water percolation and storage; and the medium potential positively influenced most of the attributes (aquifer units, uncontaminated materials, slopes, and geological formations), with land use due to agricultural practices as the only attribute with negative contribution. With this information, it is possible to develop a better land use planning, respecting the physical environment and its support capacity in order to collaborate to the management of this water source.
Processo Investigativo do Potencial de Contaminação de Aquíferos por Atividades Antrópicas da Bacia Hidrográfica do Ribeirão das Pedras (SP)
Keywords: Aquifer units; Geoenvironmental zoning; Land use planning; Multi-criteria analysis